2005
DOI: 10.1086/428037
|View full text |Cite
|
Sign up to set email alerts
|

Hot Jupiters and Hot Spots: The Short‐ and Long‐Term Chromospheric Activity on Stars with Giant Planets

Abstract: We monitored the chromospheric activity in the Ca ii H and K lines of 13 solar-type stars (including the Sun): 8 of them over 3 years at the Canada-France-Hawaii Telescope (CFHT) and 5 in a single run at the Very Large Telescope (VLT). A total of 10 of the 13 targets have close planetary companions. All of the stars observed at the CFHT show long-term (months to years) changes in H and K intensity levels. Four stars display short-term (days) cyclical activity. For two, HD 73256 and 1 Cet, the activity is likel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
317
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 265 publications
(345 citation statements)
references
References 63 publications
24
317
4
Order By: Relevance
“…Shkolnik et al (2005) appeared to confirm the result, and to find a similar effect in the υ And system. Shkolnik et al (2008) found the detections of these signals difficult to reproduce, leading them to speculate that the effect has an "on/off nature" (see Figure 2).…”
Section: Orbitally Modulated Activitysupporting
confidence: 57%
“…Shkolnik et al (2005) appeared to confirm the result, and to find a similar effect in the υ And system. Shkolnik et al (2008) found the detections of these signals difficult to reproduce, leading them to speculate that the effect has an "on/off nature" (see Figure 2).…”
Section: Orbitally Modulated Activitysupporting
confidence: 57%
“…Planet-induced activity through magnetic coupling (e.g. Shkolnik et al 2005) should be an alternative explanation of the correlation, but here it is not a very attractive one: the inner planet is at least as massive as the hypothetical 35-day planet and would, at least naively, be expected to have stronger interactions with the magnetosphere of GJ 674. The 4.69-day period, however, is only seen in the radial velocity signal, and it has no photometric or chromospheric counterpart.…”
Section: Planets Vs Activitymentioning
confidence: 94%
“…It has been speculated that similar effects, albeit on a weaker scale, may occur for stars with Hot Jupiters (Cuntz et al 2000;Lanza 2008). Observational studies have been performed on individual systems (Shkolnik et al 2005(Shkolnik et al , 2008Pillitteri et al 2011;Miller et al 2012) as well as on larger samples of planet-hosting stars (Kashyap et al 2008;Poppenhaeger et al 2010;Shkolnik 2013), finding weak correlations of stellar activity with the presence of Hot Jupiters. Indications for higher v sin i values have also been reported (Pont 2009) for systems with Hot Jupiters compared with systems hosting smaller or more distant planets, NASA Sagan Fellow yielding first indications of a tidal influence of exoplanets on their host stars.…”
Section: Introductionmentioning
confidence: 99%